KEOTENTIKAN AJARAN TASAWUF - Dimyati Sajari (Jurnal Dialog, 2015)
The accusation against the authenticity of tasawuf (Islamic mysticism or Sufism) teachings still lingers on in this contemporary era. This article contributes on answering this accusation by revisiting the nature and the origin of tasawuf. By examining the history of tasawuf, this article argues that the accusation is not true and cannot be proven. Though there is some evidence that external influence occurs, this only touches the surface (in the form of zuhud movement) not in the essence of the Sufism teaching. Therefore it can be concluded that Sufism is authentically Islamic teaching originally from Quran and hadiths, thus it is not transferred to Islam.